Hormone-Producing Ability of Testes Organ Culture in Adult Rats Under Co-culturing and Allotransplantation - Pakhomov, A. V.; Bozhok, G. A.; Legach, E. I. (Problems of Cryobiology and Cryomedicine, 2004)
The hormone-producing ability of testes organ culture of adult rats (TOCAR) under co-culturing and allotransplantation with organ culture of adrenal glands of adult rats (OCAGAR) and pituitary explant (PE), was investigated. A decrease in secretory abilities of TOCAR, co-cultured with OCAGAR and PE, was demonstrated. The following co-transplantation of these cultures did not either result in the augmentation of testosterone level in blood of orchiectomized rats. However, the combined allotransplantation of TOCAR and OCAGAR, cultured separately, resulted in a subnormal hormone level recovery in orchiectomized animals.